A biogeographical perspective on species abundance distributions: recent advances and opportunities for future research. (19th April 2017) - Matthews, Thomas J.; Borges, Paulo A.V.; de Azevedo, Eduardo Brito; Whittaker, Robert J.
Abstract: It has become increasingly recognized that multiple processes can generate similar shapes of species abundance distributions (SADs), with the result that the fit of a given SAD model cannot unambiguously provide evidence in support of a given theory or model. An alternative approach to comparing the fit of different SAD models to data from a single site is to collect abundance data from a variety of sites, and then build models to analyse how different SAD properties (e.g. form, skewness) vary with different predictor variables. Such a biogeographical approach to SAD research is potentially very revealing, yet there has been a general lack of interest in SADs in the biogeographical literature. In this Perspective, we address this issue by highlighting findings of recent analyses of SADs that we consider to be of intrinsic biogeographical interest. We use arthropod data drawn from the Azorean archipelago to further highlight how analyses of SAD form and function may be biogeographically informative. We hope that, by reviewing a number of novel approaches, our article may prove to be a catalyst for a greater interest in analysing SADs in biogeography.